Analgesic Self-Medication among Medical Students in Omar Al-Mukhtar University - Hajer Omar; Asma Omar; Mahmoud Elderbi; Mabroka Omar; Marwa Faraj; Aisha Abdulhamid (AlQalam Journal of Medical and Applied Sciences, 2024)
Analgesic self-medication is a fairly common behavior around the world, it is affected by many factors, such as; family, society, drug availability, self-care orientation, level of medical education, and illness awareness. The excessive as well as inappropriate consumption of analgesic gives rise to many problems such as peptic ulcer and nephropathy. This issue is more worsen in developing countries or places where the analgesic can be purchased without prescription such as in Libya. This research was performed to evaluate the possible reasons, prevalence, awareness as well as knowledge about consumption of analgesics without a prescription between the medical students in faculty of medicine, Omar Al-Mukhtar University. This is study was carried out during the period from7/2/2022 to 15/3/2022 in Omar Al-Mukhtar University, Al-Bayda city in Libya targeting 340 medical student who received electronic and handed questionnaires. Our study showed that 66.17% of participants were female and 33.53% were male. The prevalence of students use analgesics without prescription was (70.62%) and 53.41% of the students knew that self-medication with analgesics may affect their health negatively, (3.26%) of them had side effects and (57.27%) of them have been checked the expiry date before using analgesic. The main source of analgesics was a recommendation of a pharmacist (38.49%). The most analgesic used for self-medication was Acetaminophen (41.08%) followed by Ketoprofen (19.92%). The common causes for consuming analgesic without prescription were Headache (24.90%) followed by Dysmenorrhea (18. 26 %) and toothache (12.45%). 47.22% of the students was previous experience of using a particular analgesic. The study revealed that the prevalence of using analgesic between medical students is relatively inflated. It is mandatory to educate health sciences students about misusing and risks of self-administration as well as further researches are needed to investigate the prevalence of consumption of analgesics without a prescription between university undergraduates. التطبيب الذاتي بالمسكنات هو سلوك شائع إلى حد ما حول العالم، فهو يتأثر بالعديد من العوامل، مثل؛ الأسرة والمجتمع وتوافر الأدوية وتوجيه الرعاية الذاتية ومستوى التعليم الطبي والوعي بالمرض. الاستهلاك المفرط وغير المناسب للمسكنات يؤدي إلى العديد من المشاكل مثل القرحة الهضمية واعتلال الكلية. تزداد هذه المشكلة سوءًا في البلدان النامية أو الأماكن التي يمكن شراء المسكن فيها بدون وصفة طبية كما هو الحال في ليبيا. تم إجراء هذا البحث لتقييم الأسباب المحتملة ومدى انتشار الوعي والمعرفة حول استهلاك المسكنات بدون وصفة طبية بين طلاب الكليات الطبيةجامعة عمر المختار.أجريت هذه الدراسة خلال الفترة من 7/2/2022 إلى 15/3/2022 في جامعة عمر المختار بمدينة البيضاء في ليبيا زواستهدفت 340 طالب طب ممن تلقوا استبيانات إلكترونية و ورقية. أظهرت دراستنا أن 66.17% من المشاركين كانوا من الإناث و33.53% من الذكور. بلغت نسبة انتشار استخدام الطلاب للمسكنات دون وصفة طبية(70.62%) و53.41% من الطلاب يعرفون أن التداوي الذاتي بالمسكنات قد يؤثر على صحتهم سلباً و(3.26%) منهم لديهم آثار جانبية و(57.27%) كانو يتأكدومن تاريخ انتهاء الصلاحية قبل استخدام المسكن. المصدر الرئيسي للمسكنات كان توصية الصيدلي (%38.49) وكان المسكن الأكثر استخداماً في التداوي الذاتي هو الأسيتامينوفين (41.08%) يليه الكيتوبروفين (19.92%). الأسباب الشائعة لتناول المسكنات دون وصفة طبية هي الصداع (24.90%) يليه عسر الطمث(18.26%).وألم الأسنان (12.45%). 47.22% من الطلاب لديهم خبرة سابقة في استخدام مسكن معين. كشفت الدراسة أن معدل انتشار استخدام المسكنات بين طلاب الطب مرتفع نسبياً ومن الضروري تثقيف طلاب العلوم الصحية حول سوء الاستخدام ومخاطر الإدارة الذاتية، كما يلزم إجراء المزيد من الأبحاث للتحقيق في مدى انتشار استهلاك المسكنات دون وصفة طبية بين طلاب الجامعات